Growth Curve Modeling of Garut Sheep at UPTD-BPPTDK Margawati Garut - Nurlela, Hana; Indrijani, Heni; Heriyadi, Denie (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
Growth curves can be used to reflect changes in the body structure due to genetic and environmental responses. Here, six growth curve models are used: Gompertz, Logistic, Richard, Von Bertalanffy, Morgan-Mercer-Flodin (MMF), and Weibull models. This study aims to determine patterns and growth as seen from changes in ages and weights of male and female Garut sheep at UPTD-BPPTDK Margawati Garut. The case study method was used with 214 samples. Data from samples were processed to find similarities and curve shapes and the data was examined using Curve Expert software. The results showed that each parameter measured has a sigmoid growth curve. The curve model with the best accuracy to determine the growth rate of Garut sheep at UPTD-BPPTDK Margawati Garut is the Gompertz model, with correlation values for single birth type: average determination coefficient of 0.99, standard error of 0.98, and 0.82. For twin birth type, the average coefficient of determination is 0.99, standard errors are 0.63 and 0.57. For triplet birth type, the average coefficient of determination is 0.99, standard errors are 0.46 and 0.65.